Determination of traffic flow parameters in different traffic flow interaction cases - Junevičius, Raimundas; Bogdevičius, Marijonas (Transport, 2007)
Modelling of straight road section consisting of one traffic line gives the opportunity to simulate “follow the car” system. In general it looks like a line of vehicles, going one after another. Kinetic theory, used in this paper describes traffic flow system as a straight unbroken line with limited flow speed and concentration. Such model also gives the opportunity to derive traffic lines intersections. For example, intersection could be derived like a point with traffic lines coming and outgoing from this point by only changing boundary conditions. Mathematical model is built using characteristic method.First Published Online: 27 Oct 2010